2018
DOI: 10.1364/boe.9.000569
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse optical monitoring of peripheral tissues during uncontrolled internal hemorrhage in a porcine model

Abstract: Reliable, continuous and noninvasive blood flow and hemoglobin monitoring in trauma patients remains a critical, but generally unachieved goal. Two optical sensing methods - diffuse correlation spectroscopy (DCS) and diffuse reflectance spectroscopy (DRS) - are used to monitor and detect internal hemorrhage. Specifically, we investigate if cutaneous perfusion measurements acquired using DCS and DRS in peripheral (thighs and ear-lobe) tissues could detect severe hemorrhagic shock in a porcine model. Four animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…These conclusions are in accordance with previous findings regarding the accuracy absolute flow rates vs. relative flow at longer SDS [13,16,53]. Our results support findings from recent studies, where Equation (2) was successfully used to examine relative changes in DCS flow coefficients from both simulations and in vivo studies in animal models, at short SDS [27,28,30,31]. However, our findings also indicate that quantification of relative perfusion changes reported by these studies would be estimated more accurately, if the relative changes in perfusion at the short SDS channels were computed with MC-derived correction factors with corresponding changes in media optical properties they measured.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These conclusions are in accordance with previous findings regarding the accuracy absolute flow rates vs. relative flow at longer SDS [13,16,53]. Our results support findings from recent studies, where Equation (2) was successfully used to examine relative changes in DCS flow coefficients from both simulations and in vivo studies in animal models, at short SDS [27,28,30,31]. However, our findings also indicate that quantification of relative perfusion changes reported by these studies would be estimated more accurately, if the relative changes in perfusion at the short SDS channels were computed with MC-derived correction factors with corresponding changes in media optical properties they measured.…”
Section: Discussionsupporting
confidence: 93%
“…However, there could be clinical opportunities for using endoscopically compatible DCS probes to assess tissue perfusion in vivo, which will need to use short SDS for signal acquisition. Further, recent reports have employed DCS measurements at short SDS (<1 cm) for quantifying tissue perfusion in small animal models [27][28][29][30][31]. Surprisingly, these studies all reported that the classical diffusion-theory based theoretical expression in Equation (2) still provided good parametrization of relative changes in tissue perfusion even at short SDS used.…”
Section: Introductionmentioning
confidence: 99%
“…Other technologies have been developed, such as NIRS (Near-infrared spectroscopy) and PPI (Peripheral perfusion index) [6,38]. More recently, spectrometry has been used to demonstrate an alteration of peripheral perfusion in a porcine model of hemorrhagic shock [39]. These methods are still under development, but have brought some evidence of impaired peripheral perfusion in critical patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia was maintained with sevoflurane (Sevoflo, Zoetis, Malakoff, France) in 30% oxygen, in association with an intravenous constant rate infusion (CRI) of morphine 0.1 mg.kg −1 .h −1 . The respiratory rate and tidal volume were adjusted to obtain an end tidal CO2 of 4.6-6.0 kPa (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Intravenous fluids (Lactated Ringer) were administered throughout the experiment at a basal rate of 5 ml.kg −1 .h −1 .…”
Section: Anesthetic Protocol and Surgical Preparationmentioning
confidence: 99%
“…Thi sufficiently ra al. demonstra highly anisot thicknesses as of DCS has n biological app DCS reflectan [31], mouse a [75,76] e detector rties, this error may not be negligible for studies in which the effect size of interest is small. As mentioned above, constraining g 2 fits to shorter τ may serve to improve accuracy, as these photons have traveled deeper through tissue [59] and become fully randomized before detection.…”
Section: Discussiomentioning
confidence: 99%